Time of futsal rallies and their physiological bias to the modality (Research, Society and Development, 2022)
Futsal is a modality characterized by the intermittency and oscillation in the intensity used by the athletes in the court, in this way the present study aimed to identify the times of rallies in the male futsal and its physiological bias in the modality. The data were collected through the analysis of 27 games of the AMF team (Futsal Marauense Association), a professional team that dispute the state championship, League 1, from Rio Grande do Sul. The collection was began through the analysis of the recordings of archived games team collection. The rally time has started by triggering the timer at when the ball was set into play in the different situations of the match and the same closed, at the time the ball was outside "out of play". An average of 154.7 ± 15.6 rallies per game, between 1st (75.6 ± 10.1) and 2nd (79.1 ± 9.4) times, with an average duration of 13 ”2±12”3 seconds, without which the smallest rally found was 00”25 hundredths and the longest rally time was 1'minute 47” seconds and 10 hundredths. It is correct to say that futsal presents a need to use the three sources of ATP resynthesize (phosphates, glycolytic and aerobic). However, the occurrence of many rallies within the futsal game makes the sport require specific preparation from athletes to perform at a high level.